Efficacy of Autologous Platelet-Rich Plasma Combined With Ablative Fractional Carbon Dioxide Laser for Acne Scars: A Systematic Review and Meta-Analysis. (27th February 2019) - Chang, Hua-Ching; Sung, Chih-Wei; Lin, Ming-Hsiu
Abstract: Background: Acne scars are common and challenging clinical complications of acne vulgaris. Ablative fractional carbon dioxide (CO2 ) laser is a well-established treatment for acne scars; however, some postlaser adverse effects have been noted. Autologous platelet-rich plasma (PRP) can improve tissue regeneration. Several studies have investigated the efficacy of combination therapy of CO2 laser and PRP for acne scars. Objectives: The authors sought to conduct a meta-analysis of the efficacy of PRP combined with ablative fractional CO2 laser for treating acne scars by examining clinical trial results. Methods: A systematic review was performed by searching PubMed, Embase, Cochrane Library, and Web of Science, and a meta-analysis was conducted to assess the clinical outcomes after combination therapy of PRP and ablative fractional CO2 laser compared with laser alone. Results: We identified 4 eligible studies for the meta-analysis, including 3 randomized controlled trials. Our results demonstrated that clinical improvement after combination therapy was significantly higher than that after laser alone (odds ratio = 2.992, P = 0.001). Regarding major side effects, patients who underwent combination therapy experienced significantly shorter duration of crust compared with CO2 laser alone (standard mean difference = −1.140, P < 0.001); relatively shorter durations of erythema and edema were also noted after combination therapy. Furthermore, patient satisfaction rates were significantly higher after combination therapy than after laser alone (odds ratio = 3.169, P = 0.002). Conclusions: The combination of autologous PRP and ablative fractional CO2 laser has synergistic positive effects on the clinical outcomes for acne scars and can accelerate the recovery of laser-damaged skin. Level of Evidence: 2: